Coexistence of three mephitids in Tehuacán-Cuicatlán Biosphere Reserve, México - Farías-González, Verónica; Hernández-Mendoza, Karen Haydee (THERYA, 2021)
Three species of mephitids coexist in the Tehuacán-Cuicatlán biosphere reserve (TCBR) and belong to a guild of mammalian carnivores that feed mainly on invertebrates. To infer the interspecific interactions that allow coexistence, we aimed to compare activity patterns and abundance of hog-nosed skunk (Conepatus leuconotus), hooded skunk (Mephitis macroura), and southern spotted skunk (Spilogale angustifrons) in a tropical dry forest with ecological integrity. We analyzed activity patterns and overlap, and compared the relative abundance index (IAR) of mephitids, between rainy and dry seasons and among species, and used 235 records for C. leuconotus, 39 for M. macroura, and 42 for S. angustifrons from 15 camera-trap stations in Mount Tepetroja, Puebla, from May 1st, 2013 to April 30th, 2020. The three mephitids were active mainly during the nocturnal period, although C. leuconotus showed a unimodal pattern with activity peak around midnight, M. macroura had a bimodal pattern with activity peaks during the crepuscular hours at sunset and sunrise, and S. angustifrons had a unimodal pattern with activity peak around 2:00 a.m. Mean activity of C. leuconotus (ÂµÂ±SE = 00:42 Â± 00:12 h) and M. macroura (01:02 Â± 00:33 h) were similar (P = 0.32), and differed from the mean activity of S. angustifrons (01:49 Â± 00:23 h, P = 0.02). C. leuconotus had the highest IAR (2.53 to 7.90) and differed from M. macroura (0.44 to 1.21) and S. angustifrons (0.83 to 0.96) in both seasons (P < 0.01). C. leuconotus and M. macroura showed higher IAR during the rainy season, in contrast with S. angustifrons that had no differences in IAR between seasons. The mephitids presented temporal segregation and variability in seasonal abundance as coexistence mechanisms. S. angustifrons showed the most restricted circadian activity and avoided the other two mephitidsâ€™ activity peaks. C. leuconotus was the most abundant species; thus, we inferred that the hog-nosed skunk determined the dynamics of intraguild interactions among mephitids in the tropical dry forest in the TCBR. Three species of mephitids coexist in the Tehuacán-Cuicatlán biosphere reserve (TCBR) and belong to a guild of mammalian carnivores that feed mainly on invertebrates. To infer the interspecific interactions that allow coexistence, we aimed to compare activity patterns and abundance of hog-nosed skunk (Conepatus leuconotus), hooded skunk (Mephitis macroura), and southern spotted skunk (Spilogale angustifrons) in a tropical dry forest with ecological integrity. We analyzed activity patterns and overlap, and compared the relative abundance index (IAR) of mephitids, between rainy and dry seasons and among species, and used 235 records for C. leuconotus, 39 for M. macroura, and 42 for S. angustifrons from 15 camera-trap stations in Mount Tepetroja, Puebla, from May 1st, 2013 to April 30th, 2020. The three mephitids were active mainly during the nocturnal period, although C. leuconotus showed a unimodal pattern with activity peak around midnight, M. macroura had a bimodal pattern with activity peaks during the crepuscular hours at sunset and sunrise, and S. angustifrons had a unimodal pattern with activity peak around 2:00 a.m. Mean activity of C. leuconotus (Âµ Â± SE = 00:42 Â± 00:12 h) and M. macroura (01:02 Â± 00:33 h) were similar (P = 0.32), and differed from the mean activity of S. angustifrons (01:49 Â± 00:23 h, P = 0.02). C. leuconotus had the highest IAR (2.53 to 7.90) and differed from M. macroura (0.44 to 1.21) and S. angustifrons (0.83 to 0.96) in both seasons (P < 0.01). C. leuconotus and M. macroura showed higher IAR during the rainy season, in contrast with S. angustifrons that had no differences in IAR between seasons. The mephitids presented temporal segregation and variability in seasonal abundance as coexistence mechanisms. S. angustifrons showed the most restricted circadian activity and avoided the other two mephitidsâ€™ activity peaks. C. leuconotus was the most abundant species; thus, we inferred that the hog-nosed skunk determined the dynamics of intraguild interactions among mephitids in the tropical dry forest in the TCBR.